Pembelajaran Seni Bahasa dalam Konteks Lintas Kurikulum melalui Drama - Rin Surtantini (Jurnal Kajian Seni, 2016)
Everyone is entitled to draw on the arts elements to create and give meanings, toexpress themselves, to communicate and share the meanings with other people, andto understand the world around them. Activities related to arts belong to every humanbeing, and anything refl ected in arts is about human being. In the context of crosscurriculum,arts can be creatively woven into other subject areas, or is linked with a widevariety of subjects in the educational program. As one of the school subject, languagearts is the vehicle of communication by which we live, work, share, and build ideas andunderstandings of the present, refl ect on the past, and imagine the future. Languagearts incorporates the integrated teaching and learning of oral, written, and visual textsthrough reading, writing, speaking, listening, and viewing. The paper highlights drama asan alternative of arts activity integrated in a cross-curricular language arts program.